2021
DOI: 10.21037/tlcr-20-812
|View full text |Cite
|
Sign up to set email alerts
|

Cholesterol synthesis disruption combined with a molecule-targeted drug is a promising metabolic therapy for EGFR mutant non-small cell lung cancer

Abstract: Background: Acquired resistance is a challenge for epidermal growth factor receptor (EGFR) mutant nonsmall cell lung cancer. Here, we propose a novel treatment strategy based on recent lipid metabolism work. Methods:We applied a variety of experimental methods such as immunoblotting, MTT, si-RNA, and animal models, to demonstrate the relationship between EGFR and low-density lipoprotein receptor (LDLR) and the effects of statin monotherapy, and TKI monotherapy, and their combination on cell proliferation at th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 30 publications
(23 reference statements)
0
14
0
Order By: Relevance
“…Cholesterol as an important component of lipids contribute to rapid cancer cell growth, metastasis and drug resistance [ 41 ]. Recently, the alteration of cholesterol homeostasis was reported in NSCLC as a result of dysregulation in cholesterol synthesis, uptake or trafficking process [ 17 , 42 ]. In the present study, we found upregulated cholesterol level in both gefitinib-resistant PC-9/GR, H1975 cells and osimertinib-resistant PC-9/OR cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cholesterol as an important component of lipids contribute to rapid cancer cell growth, metastasis and drug resistance [ 41 ]. Recently, the alteration of cholesterol homeostasis was reported in NSCLC as a result of dysregulation in cholesterol synthesis, uptake or trafficking process [ 17 , 42 ]. In the present study, we found upregulated cholesterol level in both gefitinib-resistant PC-9/GR, H1975 cells and osimertinib-resistant PC-9/OR cells.…”
Section: Discussionmentioning
confidence: 99%
“…Most recently, content of cholesterol is found to be upregulated in NSCLC cells or tumor xenograft models that resistant to the first-generation EGFR-TKIs as the result of increased biosynthesis, uptake and receded efflux. Accumulation of cholesterol is regarded as an important factor of resistance to the first-generation EGFR-TKIs [ 17 19 ]. However, the mechanisms of cholesterol confer resistance to EGFR-TKIs are not well-revealed.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, another inhibitor, simvastatin, induced apoptotic cell death in EGFR-mutated, gefitinib-resistant H1975 NSCLC cells by upregulating the pro-apoptotic Bcl-2 family member BIM [119]. Moreover, atorvastatin enhanced the anti-proliferative effect of gefitinib and osimertinib in TKI-sensitive, EGFR-mutated NSCLC models and overcame EGFR gefitinib resistance in H1975 cells [83].…”
Section: Targeting Cholesterol Metabolismmentioning
confidence: 94%
“…Moreover, LDLR (low-density lipoprotein receptor) was highly expressed in EGFRmutated NSCLC cells, suggesting a role of EGFR signaling in upregulating LDLR expression through an AKT-mediated, SREBP1-dependent pathway [83].…”
Section: Cholesterol Metabolismmentioning
confidence: 99%
“…Another study identified a higher expression of low-density lipoprotein receptor (LDLR) mediated by sterol regulatory-element-binding protein 1 (SREBP1) in EGFR -mutant LUAD cells compared to wild type (wt). Combinatorial treatment of ATV and EGFR TKIs resulted in higher inhibition than single treatment, highlighting the importance of lipid biosynthesis in EGFR TKI resistance [ 43 ]. Generally, elevated rates of lipogenesis are a characteristic of numerous tumors while SREBP1-mediated constitutive lipogenesis is one of the main characteristics of EGFR TKI-resistant LUAD cells and might represent a promising druggable target for overcoming the resistance [ 44 , 45 ].…”
Section: Egfr Tki Resistance and Fatty Acid Metabolismmentioning
confidence: 99%